TOTAL PLATE COUNT ON SMOKED CATFISH IN PANORAMA MARKET BENGKULU CITY DURING STORAGE ROOM TEMPERATURE - Tuti Tutuarima (Jurnal Agroindustri, 2016)
The purpose of this study was to evaluate the quality of smoked catfish are traded on the Panorama Market Bengkulu City seen from the total of microorganisms during storage at room temperature. This study uses a combination of exploratory sequential model (combining qualitative and quantitative research methods, respectively). Samples were taken from merchants of smoked catfish in the Panorama Market Bengkulu City. Storage of samples carried out for 21 days. Analysis of total plate count (TPC) was conducted in the Laboratory Protection UNIB. Quality parameters used refer to SNI 2725.1: 2009 on quality requirements of smoked fish. Determination of total plate count was performed according to SNI 01-2332.3-2006. Each sample testing was done 2 replications. ALT test results show an increasing number of microbes during storage. ALT value on day 0 of storage in the range of 8.2 x 104 colonies/g - 1.4 x 106 colonies/g, whereas on day 21 ranged from 2.0 x 106 colonies/g - 3.9 x 106 colonies/g. The high value of ALT is caused by the processing, packaging, transportation, storage conditions, as well as the manner of presentation for sale on the market. Microorganism contamination will increase with increasing chain length distribution.